Obesity and Asthma: Nutrition Risk Factors In Adolescents - Franceliane, Jobim Benedetti; Vera, Lúcia Bosa; Juliana, Mariante Giesta; Gilberto, Bueno Fischer (International Journal of Nutrition, 2016)
The objective of this study was to confirm the nutritional risk factors for asthma and obesity in adolescents using a cross-sectional survey. We included male and female adolescents aged 10 to 19 years of age in this study. The indicators of nutritional status used in this study were body mass index, the height-for-age index, and arm and waist circumferences. We used a food frequency questionnaire to estimate the average consumption of sodium. Physical activity was assessed using the International Physical Activity Questionnaire, and asthma characteristics were evaluated using the International Study of Asthma and Allergies in Childhood (ISAAC). Factors associated with asthma in bivariate and multivariate analyses were assessed using the Poisson regression analysis. The significance level was set at 5%, and the analyses were performed using the SPSS statistical package. We evaluated 1362 students with an average age of 15.65 ± 1.24 years. There was a positive risk for asthma between females (PR = 1.41) and asthma severity in adolescents with a high sodium intake (PR = 2.30). Within overweight adolescents, the prevalence for asthma risk washigher among females (PR = 1.66) and the high sodium intake group (PR = 1.98). An increased risk for asthma severity correlated with high sodium intake (PR = 3.07). There was a higher risk for asthma and its severity in females with high sodium intake. The same pattern was observed for adolescents with excessive weight.
Keywords: adolescents; asthma; obesity; sodium; physical activity.